2011
DOI: 10.1007/s13318-011-0068-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the rapidity of onset of the therapeutic effect between nateglinide and mitiglinide by PK/PD analysis in rats

Abstract: Nateglinide and mitiglinide are immediate short-acting insulinotropic agents. Both are administered preprandially to control postprandial hyperglycemia. Glinide drugs are characterized by immediate onset as well as rapid disappearance of effect as compared with sulfonylurea drugs. We examined the rapidity of onset of the therapeutic effect between nateglinide and mitiglinide by pharmacokinetic/pharmacodynamic analysis using the receptor-binding-dissociation model in rats. Nateglinide or mitiglinide was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Toshiyuki Takanohashi et al reported the pk-pd. modeling methodology to describe the rapidity therapeutic effect of mitiglinide by using the receptor-binding-dissociation in rats [12]. However, model of inhaled glucose in healthy humans has not been published previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toshiyuki Takanohashi et al reported the pk-pd. modeling methodology to describe the rapidity therapeutic effect of mitiglinide by using the receptor-binding-dissociation in rats [12]. However, model of inhaled glucose in healthy humans has not been published previously.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma mitiglinide concentration was determined by the modification of the methods of Yu and Takanohashi [9, 12]. A 1200 HPLC system (Agilent technologies, Palo Alto, CA, USA) coupled with a triple-quadrupole tandem API 4000 mass spectrometer (AB/MDS-Sciex, Concord, Ontario, Canada) were used for analysis.…”
Section: Methodsmentioning
confidence: 99%